Utilizing Local Communities towards the Marketability of EDC-UUM: A Supply Chain Model - Engku Muhammad Nazri Bin Engku Abu Bakar; Masnita Misiran; Suzzaini Abdullah (International Journal of Supply Chain Management, 2015)
This study proposes a supply chain model for the Excecutive Development Center of Universiti Utara Malaysia (EDC-UUM) to enhance the usability and the visibility of EDC-UUM, thus increasing the demand for EDC-UUM services and indirectly, the profit as well. Specifically, this study embarks on two objectives which are to determine the resources available and opportunities that can be grabbed to strengthen the functions and usability of EDC-UUM and to develop a supply chain model for EDC-UUM that will incorporate all the resources and opportunities so that the demand for and the utilization of the training/seminar rooms and hotel rooms increases. To achieve the first objective, a SWOT analysis was conducted by assessing the current practice and future plans of EDC-UUM. The second objective was achieved by studying the characteristic of a hotel supply chain, and then mapping the supply chain to suit the characteristics of EDC-UUM. In this report, the supply chain model focuses only on the first tier for EDC-UUM's product development that directly involves the use of local community members.